Heterotopias in residual urban areas as creative communication practices (Comunicação & Inovação, 2024)
This article brings the notion of heterotopia closer to the creation of heterogeneous relationships with symbolic urban spaces and movement, which are constantly configured and reconfigured in the processes of communication and redesign of ways of inhabiting the city. We argue that the heterotopic experience sets in motion a network of alliances aimed at transformation and re-existence. In residual urban areas, the existence of heterotopias is linked not to the search for a lost "paradise", but to the creation of safe spaces that put at risk the asymmetries of power that permeate the lives of subjects and their network of affections. We analyze, based on a case study, how the construction of a garden can change the possibilities of agency of subjects in vulnerable situations, redefining the bonds of interdependence, everyday practices and historically situated imaginaries. We try to think of the garden and also gardening as the heterotopic practice of resignifying urban space and transforming oneself and bonds with others. The gardener's care is also an ethical and political gesture that organizes the sharing of responsibilities through openness to all otherness.
Keywords: Heterotopia; Experimentation; Urban gardens.